Analysis of the Correlation Between Vibrations and the Number of Shorted Turns in the Stator Winding of a Squirrel-Cage Induction Motor - Marczak, Mikołaj; Pietrowski, Wojciech; Górny, Konrad (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Helsinki, Finland. E-mail: juhani.mantere@fi.abb.comThis paper presents a method for diagnosing a squirrel cage induction machine based on machine vibration analysis. The study focuses on the consideration of a winding fault in the stator winding of an induction machine. The case of a winding fault in one phase was considered. The machine vibration signal was recorded at a constant load torque. Wavelet packet decomposition was used to analyse the recorded vibration signals. The results of the wavelet analysis were correlated with the number of shorted windings. The result was a method for detecting faults in an electrical circuit using the vibration signal.